Hydrometeorological Disasters in Central Aceh in 2025:A Qualitative Analysis of Impacts and Mitigation Strategies - Hernita Nita; Husrin Konadi; Riyan Pujiono (Insight: Journal of Counseling and Psychology, 2026)
Hydrometeorological disasters in Central Aceh in 2025, in the form of flash floods and landslides affecting the districts of Ketol, Kebayakan, and Sekeliling, caused dozens of fatalities, damage to settlements, and the disruption of road access and vital infrastructure; this study aims to analyze the qualitative impacts and mitigation strategies to strengthen the resilience of mountain communities. The method used is a qualitative approach through in‑depth interviews with 20 household heads affected by the disaster, representatives of the local government, and analysis of disaster‑management documents from the Central Aceh Disaster Management Agency and emergency‑response records from November–December 2025. The results indicate that the main impacts include psychological trauma, loss of agricultural livelihoods, and damage to road, bridge, and irrigation infrastructure; meanwhile, strong triggering factors include unstable soil, changes in land use, and an underdeveloped early‑warning system in mountainous areas. The main conclusion states that effective disaster mitigation requires a combination of strengthened local institutions, ecosystem restoration, and active community participation in mitigation planning. The key recommendations include the establishment of disaster‑resilient villages, the relocation of settlements to safer areas, and the enhancement of capacity among local officials and volunteers in dealing with hydrometeorological emergencies in Central Aceh.